Chorizococcus (Hemiptera: Pseudococcidae), un nuevo registro para Cuba - Blanco, E.=700 1 Sanchez, R.; Rodriguez, A.M.
(Es, En)
Ilus., 6 ref.
Keywords: HEMIPTERA; PSEUDOCOCCIDAE; ESPECIES NUEVAS; REGISTRO; CUBA; CHORIZOCOCCUS